UTeM`s Amphibious Hybrid Vehicle: Development of Hybrid Electric Propulsion System - Hassan, Muhammad Zahir; Md Isa, Amjad Saddar; Abdul Kudus, Syahibudil Ikhwan; Abdul Manaf, Muhammad Zaidan (Praise Worthy Prize, 2013)
This paper presents the preliminary development of hybrid electric propulsion system for amphibious hybrid vehicle (AHV). AHV is developed as a transportation that can operate on land and water which to be used by rescue team in rescue operations. AHV is driven by motor electric on the land, and while on the water, AHV is propelled by internal combustion engine (ICE) and at the same time, ICE is use as generator to generate the electricity to recharge the battery pack. The main factors that need to be considered in order to develop a hybrid electric propulsion system is the power required by batteries to transmit to the motor electric to move the vehicle. An optimum hybrid electric propulsion system should have minimum fuel consumption, simple to develop and high reliability. Matlab Simulink Analysis based on the mathematical modelling is conducted to determine the power required before the fabrication take place. The design of hybrid electric propulsion is then fabricated by combination of ICE and electric motor. Finally experimental analysis is conducted to determine its reliability and durability.